Detecting Similarities in Posts Using Vector Space and Matrix - Haq, Al Fataa Waliyyul; Carinia, Ema; supian, sudradjat; subiyanto, subiyanto (iora, 2020)
This study discusses the application of two linear algebraic materials, namely vector and matrix spaces. The application of the two materials is related to an article, the writing can be in the form of an article, book, and so on. The writings examined in this study use example sentences made by the author. Two materials of linear algebra, namely the vector space and the matrix are used to analyze whether there is a similarity between the writing made with other writing. As a result, vector space and matrix can be used to detect similarities in a text.